A Synthesis of Deglacial Deep‐Sea Radiocarbon Records and Their (In)Consistency With Modern Ocean Ventilation. Issue 2 (3rd February 2018) - Zhao, Ning; Marchal, Olivier; Keigwin, Lloyd; Amrhein, Daniel; Gebbie, Geoffrey
Abstract: We present a synthesis of 1, 361 deep‐sea radiocarbon data spanning the past 40 kyr and computed (for 14 C‐dated records) from the same calibration to atmospheric 14 C. The most notable feature in our compilation is a long‐term Δ 14 C decline in deep oceanic basins over the past 25 kyr. The Δ 14 C decline mirrors the drop in reconstructed atmospheric Δ 14 C, suggesting that it may reflect a decrease in global 14 C inventory rather than a redistribution of 14 C among different reservoirs. Motivated by this observation, we explore the extent to which the deep water Δ 14 C data jointly require changes in basin‐scale ventilation during the last deglaciation, based on the fit of a 16‐box model of modern ocean ventilation to the deep water Δ 14 C records. We find that the fit residuals can largely be explained by data uncertainties and that the surface water Δ 14 C values producing the fit are within the bounds provided by contemporaneous values of atmospheric and deep water Δ 14 C. On the other hand, some of the surface Δ 14 C values in the northern North Atlantic and the Southern Ocean deviate from the values expected from atmospheric 14 CO2 and CO2 concentrations during the Heinrich Stadial 1 and the Bølling‐Allerød. The possibility that deep water Δ 14 C records reflect some combination of changes in deep circulation and surface water reservoir ages cannot be ruled out and will need to be investigated with a more complete model. Key Points: Published and new deep ocean radiocarbon records for the past 40 kyr are compiled A 16‐box model of modern ventilation is fit to the deglacial data The residuals of the fit can generally be explained by data uncertainties